Teknik Relaksasi Pernapasan terhadap Frekuensi Berkemih pada Lansia - Andri Kusuma Wijaya; Nurhayati Nurhayati; Selvia Novitasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of breathing relaxation techniques on the frequency of urination or urinary incontinence for the elderly at the Tresna Werdha Pagar Dewa Social Home Bengkulu. This study used a one-group pretest-posttest pre-experimental research design. The results of the study found that most of the respondents were female, namely 9 (60%) and male, 6 (40%), while based on education level, most of the respondents had a low level of education, namely 13 (86.7%) for higher education. there are 2 respondents (13,3%). The results of the bivariate analysis of breathing relaxation techniques on the frequency of urination in the elderly (p-value = 0.000). In conclusion, there is an effect of the Breathing Relaxation Technique on the Frequency of Urination in the Elderly at the Tresna Werdha Pagar Dewa Social Institution, Bengkulu. Keywords: BAK, Relaxation